Effect of 30°C Heat on the Anaerobic Capacity of Heat Acclimatised Athletes - Finn, James P. (Asist Group, 2003)
The main finding of this study was that for heat acclimatised athletes, there was no significant difference (p=0.58) in anaerobic capacity for temperate (21.8 ± 0.5 °C; 52 ± 5 % relative humidity) compared with warm conditions (29.6 ± 0.5 °C; 51 ± 9 % relative humidity). Anaerobic capacity was estimated using the maximal accumulated oxygen deficit (MAOD) during constant intensity cycling at 120% peak rate of O(2) consumption until exhaustion. This yielded mean MAOD values of 3.3 ± 0.9 and 3.5 ± 1.1 L for temperate and warm conditions, respectively. Peak post-exercise lactate values of 14.7 ± 3.8 and 14.4 ± 4.5 mmol·L(-1) for temperate and warm conditions respectively, were also not significantly different (p=0.72). Time to exhaustion (TTE) was similarly unchanged (p=0.56), being 175 ± 19 and 170 ± 18 s for temperate and warm conditions, respectively. These results suggest that the MAOD remains a valid test throughout environmental temperatures for the range of 20-30 °C when used with heat acclimatised athletes.